New results on the degree-diameter problem for undirected graphs - Comellas, Francesc (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2025)
This paper presents fourteen newly discovered largest undirected graphs with specified degree and diameter, identified since the publication of the comprehensive survey by M. Miller and J. Širáň (Electron. J. Combin. DS14, 2nd. edition. May 2013). These findings advance the longstanding investigation of the degree-diameter problem, a key topic in graph theory, and offer a fresh insight for both theoretical research and practical applications in network design and combinatorial optimization.